Multiple linear regression analyses of the performance and profitability of the Czech banking sector - Petra Jilkova; Pavla Kotatkova Stranska (Institute of Economic Research (IER), 2017)
The global financial crisis started in the USA and extended to the European market in 2009 - 2010 and caused significant problems in the banking sector. Czech banks were not significantly affected and recorded a profit in many cases and there was no need for government intervention. The purpose of this paper is to analyze the effect of the economic situation of the Czech Republic on the performance and profitability of the banking market through selected determinants. Constructing a linear regression model predicts the values of the dependent variable from the variability of the values of the independent variables. In particular, the final report focusses on measuring the performance and profitability of the banking sector using the method of 'Multiple linear regression'. The basis for multiple linear regression model is to estimate the effect of each independent variable Xi to the dependent variable Y. The force of the impact, determine the regression coefficients betha, also determining which independent variables have the greatest and the smallest effect on the dispersion of the dependent variables. In other words, how much of the variance of the dependent variable is explained by selected independent variables. In addition, a literature review and analysis of secondary are based on data published on or before 1. February 2017. This paper clarifies the structure of the Czech banking sector and it is focused on the performance and profitability in the defined time period and how it compares with the selected banking sector and indicators in other countries. On account of data availability for all the years examined, only selected banks were included.
Keywords: G21; M31; C38; O16; 330; bank; financial sector; linear regression analyses; performance; profitability